Total Body Irradiation in Haematopoietic Stem Cell Transplantation for Paediatric Acute Lymphoblastic Leukaemia: Review of the Literature and Future Directions - Bianca A. W. Hoeben (Frontiers Media S.A., 2021)
Total body irradiation (TBI) has been a pivotal component of the conditioning regimen for allogeneic myeloablative haematopoietic stem cell transplantation (HSCT) in very-high-risk acute lymphoblastic leukaemia (ALL) for decades, especially in children and young adults. The myeloablative conditioning regimen has two aims: (1) to eradicate leukaemic cells, and (2) to prevent rejection of the graft through suppression of the recipient's immune system. Radiotherapy has the advantage of achieving an adequate dose effect in sanctuary sites and in areas with poor blood supply. However, radiotherapy is subject to radiobiological trade-offs between ALL cell destruction, immune and haematopoietic stem cell survival, and various adverse effects in normal tissue. To diminish toxicity, a shift from single-fraction to fractionated TBI has taken place. However, HSCT and TBI are still associated with multiple late sequelae, leaving room for improvement. This review discusses the past developments of TBI and considerations for dose, fractionation and dose-rate, as well as issues regarding TBI setup performance, limitations and possibilities for improvement. TBI is typically delivered using conventional irradiation techniques and centres have locally developed heterogeneous treatment methods and ways to achieve reduced doses in several organs. There are, however, limitations in options to shield organs at risk without compromising the anti-leukaemic and immunosuppressive effects of conventional TBI. Technological improvements in radiotherapy planning and delivery with highly conformal TBI or total marrow irradiation (TMI), and total marrow and lymphoid irradiation (TMLI) have opened the way to investigate the potential reduction of radiotherapy-related toxicities without jeopardising efficacy. The demonstration of the superiority of TBI compared with chemotherapy-only conditioning regimens for event-free and overall survival in the randomised For Omitting Radiation Under Majority age (FORUM) trial in children with high-risk ALL makes exploration of the optimal use of TBI delivery mandatory. Standardisation and comprehensive reporting of conventional TBI techniques as well as cooperation between radiotherapy centres may help to increase the ratio between treatment outcomes and toxicity, and future studies must determine potential added benefit of innovative conformal techniques to ultimately improve quality of life for paediatric ALL patients receiving TBI-conditioned HSCT.